2020
DOI: 10.1186/s12948-020-00126-5
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization to storage proteins in peanut and hazelnut is associated with higher levels of inflammatory markers in asthma

Abstract: Background: Sensitization to peanuts and hazelnuts is common among young asthmatics and can be primary or a result of cross-reactivity. Sensitization as a result of cross-reactivity to birch pollen is typically associated to tolerance or mild and local symptoms upon intake of peanut or hazelnut. Aim: The aim of this study was to investigate relationships between IgE antibody responses against peanut and hazelnut components, airway and systemic inflammation markers, lung function parameters and reported food hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
(47 reference statements)
1
6
0
1
Order By: Relevance
“…Storage protein sensitized individuals had higher levels of exhaled nitric oxide and blood eosinophil cell counts as compared to other sensitized individuals, these result is in line with Johnson et al 24 who found that storage protein sensitized individuals showed higher FENO (23.2 p vs. 16.7 ppb) compared with non‐storage protein sensitized and by Hughes et al 23 who found that in individuals with previous asthma or no current medication, the majority still had FENO >35 ppb. However, our findings of elevated FENO in storage protein sensitized individuals independent of asthma and polysensitization is new and has not been shown before.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Storage protein sensitized individuals had higher levels of exhaled nitric oxide and blood eosinophil cell counts as compared to other sensitized individuals, these result is in line with Johnson et al 24 who found that storage protein sensitized individuals showed higher FENO (23.2 p vs. 16.7 ppb) compared with non‐storage protein sensitized and by Hughes et al 23 who found that in individuals with previous asthma or no current medication, the majority still had FENO >35 ppb. However, our findings of elevated FENO in storage protein sensitized individuals independent of asthma and polysensitization is new and has not been shown before.…”
Section: Discussionsupporting
confidence: 79%
“…22 Both peanut allergic individuals with and without asthma 23 have been found to express high levels of FENO even though peanut is primarily a food and not inhalant allergen. 23,24 Johnson et al have reported that asthmatic patients aged 10-35 years, with a sensitization to peanut allergen molecules Ara h 1, h 2 and h 3 or the hazelnut storage proteins Cor a 9 and Cor a 14, were found to express higher levels of FENO than individuals without peanut sensitization, 24 especially in the youngest age group. The explanation for this is not completely understood, neither if this is a sign of airway inflammation or a systemic inflammation, and further studies are needed.…”
Section: Inflammatory Biomarkers and Systemic Inflammationmentioning
confidence: 99%
“…This underscores the previous statement that in adults, cross-reactivity between hazelnuts and birch is the main driving force of reported adverse reactions, with these sensitizations being more common in asthma. A recent study [ 49 ] showed that asthmatic individuals between 10 and 35 years of age with coexisting sensitization to peanut and hazelnut SSPs have higher levels of inflammatory markers with higher levels of a fraction of exhaled nitric oxide and blood eosinophil count.…”
Section: Natural History Of Hazelnut Allergymentioning
confidence: 99%
“…Sensitization to hazelnuts is common among young asthmatics 41 and can be a primary effect or a result of cross-reactivity. Johnson et al investigated the relationships between IgE antibody responses to hazelnut components, airway and systemic inflammation markers, and lung function parameters, and reported food hypersensitivity in a study of 408 asthmatic children and young adults in Sweden.…”
Section: Hazelnut Allergy ( Table 1 )mentioning
confidence: 99%